Giyah Supanggah: Trace of Artist of Wayang Topeng Dalang Klaten - Sri Dwi Wahyuni (Dance and Theatre Review, 2018)
The significance of this research is the transmission of cultural tradition artfrom the descendants of Makaton (Somokaton) puppeteers, namely Jaka PurwaPandaya (father) and Widhi Harsono (grandfather). As an active heir, GiyahSupanggah is a woman who becomes a puppeteer as well as dancer of wayangtopeng dalang, cut and make puppets, and deepen the knowledge and skills ofplaying gamelan. Giyah is a figure of artist who has various artistic talents andemancipation figure of Javanese women of her times. As a mask puppet dancer,she is committed to preserving and developing the genre of performing artsin order to survive and thrive. Giyah’s integrity is shown in the art activitiesby establishing Sanggar Sekar Kedhaton in her home. It is expected that thetransmission of culture among the younger generation as the successor oftraditional art can take place. The present study belongs to a qualitative researchemploying descriptive-analysis based on anthropological approach. It focuseson the analysis of internalization process, socialization, and enculturation thatform Giyah as an active heir of puppeteer and dancer of wayang topeng dalangfrom Klaten. The qualification of Giyah as a puppeteer and dancer contributesto the preservation of traditional art marked by her reputation as a public figureof a traditional artist. The purpose of this study is to know and describe the roleof Giyah as a bearer of traditional art as a legacy of local wisdom. The benefitis to reveal the existence of a forum of creativity for the younger generation inan effort to preserve and develop the art of tradition in order not to be extinctfaded by the times.Keywords: Giyah Supanggah; female puppeteer; wayang topeng dalang